C. Lloyd Morgan correspondence - Morgan, C. Lloyd (Conwy Lloyd), 1852-1936.
ALS (1926 May 26) from Morgan to F. Bernhard Vesper regarding psychical research.
British psychologist and zoologist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Vesper, F. Bernhard -- Correspondence; Parapsychology -- Research; Psychologists; Zoologists